2021
DOI: 10.1093/ckj/sfab199
|View full text |Cite
|
Sign up to set email alerts
|

Early and late acute kidney injury: temporal profile in the critically ill pediatric patient

Abstract: Background Increasing AKI diagnosis precision to refine the understanding of associated epidemiology and outcomes is a focus of recent critical care nephrology research. Timing of onset of acute kidney injury (AKI) during pediatric critical illness and impact on outcomes has not been fully explored. Methods Secondary analysis of the Assessment of Worldwide Acute Kidney Injury, Renal Angina, and Epidemiology (AWARE) database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Evaluation of the magnitude of FO over the temporal trajectory of an ICU stay may further delineate these targets for clinical intervention. A recent publication by Ruth et al (20) evaluated this concept as it pertains to acute kidney injury (AKI) in a secondary analysis of the Assessment of Worldwide Acute Kidney Injury, Renal Angina, and Epidemiology (AWARE) study. This study showed that factors such as timing, trajectory, duration, and magnitude of AKI collectively impact outcomes (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the magnitude of FO over the temporal trajectory of an ICU stay may further delineate these targets for clinical intervention. A recent publication by Ruth et al (20) evaluated this concept as it pertains to acute kidney injury (AKI) in a secondary analysis of the Assessment of Worldwide Acute Kidney Injury, Renal Angina, and Epidemiology (AWARE) study. This study showed that factors such as timing, trajectory, duration, and magnitude of AKI collectively impact outcomes (20).…”
mentioning
confidence: 99%
“…The AWARE study is an international multicenter study of critically ill children and young adults designed to evaluate the epidemiology and impact of AKI and FO (20,(23)(24)(25)(26)(27). This planned secondary analysis aims to: 1) describe the epidemiology of FO and 2) determine the association between FO magnitude (peak FO) and of FO ≥ 5% and FO ≥ 10% at the end of ICU Day1 and 2, with outcomes (AKI on day 3, 28-d ventilation-free days [VFDs], 28-d ICU-free days, and 28-d mortality).…”
mentioning
confidence: 99%
“…These definitions are agnostic to etiology, course, rate and degree of recovery, and timing of onset in relation to critical illness. Evidence is rapidly accumulating to indicate that severity is not the only dimension that has outcome implications; rather, timing of onset, duration, number of episodes, and rate of recovery, have discrete impacts on organ and global outcomes (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Renal recovery after AKI episodes is not always complete. Certain risk factors, such as extent of pre-morbid kidney health, repeat events, and underlying risk factors contribute to impaired recovery with long term consequences (22,23,25). About 10% of AKI survivors develop chronic kidney disease (CKD) (26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…FO-adjusted creatinine, which corrects measured creatinine by degree of FO, has been shown to improve prediction of postoperative AKI in adults following cardiac surgery (16). Additionally, trajectories and durations of AKI have stronger associations with poor outcome than peak severity (17)(18)(19). Given the complex interrelatedness of FO, creatinine, AKI, and outcomes, it is possible that we are systematically underestimating the true burden of AKI due to the limitations of the definitions used.…”
mentioning
confidence: 99%